A simple design of SIW horn fed multibeam transmitarray antenna using transmission matrix approach. Issue 1 (30th September 2019) - Xi, Baokun; Cai, Yang; Xue, Qianzhong; Wang, Yong; Yang, Shaopeng; Zhang, Rui
Abstract: This article develops an efficient solution to design beam‐scanning transmitarray (TA). The four‐layer unit associated with the focal planar substrate integrated waveguide (SIW) array is presented and characterized. The proposed linearly polarized TA is implemented as four‐layer sheet admittance composed of the subwavelength unit, whose transmission feature would be accurate analyzed by the equivalent circuit model. The phase layout of TA is optimized by using the PMM method in order to achieve a wide scanning behavior and reduce the scan loss. Arc‐shaped SIW horn antenna array is adopted as the feeding source. Artificial impedance surfaces printed on either side against the low‐profile substrate results in a greatly enhanced radiation performance. The TA and feeds presented at 20 GHz are both fabricated using standard PCB processing. The measured results show a greatly improved ±45° scan range with the gain loss of 0.73 dBi by switching the SIW horn antenna. Good radiation and bandwidth characters are performed in all states of operation for both ports, confirmed the effectiveness of proposed design process.